Hypnea platyclada, a new species of red alga (Rhodophyta, Cystocloniaceae) from Brazil - de Jesus, Priscila Barreto; Guimarães, Silvia Maria Pita De Beauclair; Nunes, José Marcos De Castro (Phytotaxa, 2013)
Hypnea platyclada sp. nov. is described in detail from plants collected in northeastern Brazil and compared with closely related species such as Hypnea volubilis. The new species is characterized by a cylindrical estolon and stipe, flattened upper portions, flattened fusiform branches, evident axial filament with aspect of midrib, tetrasprangia and spermatangia forming sori on one side of the branchlets, cortical cells of unequal size and lenticular thickening restricted to the extremities of the cells of the axial filament.